MEASUREMENT OF THE B-0-(B)OVER-BAR-0 MIXING PARAMETER IN DELPHI - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Almeida, F; Alvsvaag, S; Amaldi, U; et al. (1994)
A total of about 900 000 Z0 → qq decays have been analyzed to measure the B0B0 mixing probability. Two different b tagging techniques have been used: events with two leptons and events with one lepton and one Λ. From a combination of the two methods the average mixing parameter, χ, was determined to be (12.1±1.6(stat.)±0.4(syst.)±0.4(model)%. © 1994.